ANALISIS KINERJA KEUANGAN PT ALAM SUTERA Pendekatan Economic Value Added - Renny Mointi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
PT Alam Sutera with the approach of Economic Value Added (EVA), wherein the method of analysis used is descriptive quantitative by using Economic Value Added (EVA), data used is data obtained by way of documentation during the period 2010 to 2012. The analysis showed that PT Alam Sutera in 2010 to 2012 created the Economic value added is positive. This shows that the financial performance of PT Alam Sutera, using the approach of Economic Value Added (EVA) showed a good value.